2023
DOI: 10.3390/rs15184448
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Regional Patterns of Sea Level Acceleration over the China Seas

Ying Qu,
Svetlana Jevrejeva,
Shijin Wang

Abstract: Accelerated sea level rise is placing coastal communities in a vulnerable position; however, the processes underlying sea level acceleration in China remain uncertain. In this study, we examine the sea level acceleration and its contributors over the China Seas. We calculate acceleration along the Chinese coast using satellite altimetry and tide gauge records. During the satellite altimetry era, sea level acceleration from tide gauge records varies across all stations, reaching up to 0.30 ± 0.20 mm/yr2, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…In Figure 7D, the lines following the LVs and PCTS recombination and the adjusted steric component are fitted to the curves, peaking around 2010, with a proportion ranging from 20% to 25%, with an average value of 11.17%, in line with the findings of Qu et al (2019). Previous studies also found that increasing ocean mass accounts for a greater proportion of the drivers of sea level change in the BYECS, and it dominates the contribution to the change in sea level trend (Chang et al, 2017;Qu et al, 2023).…”
Section: Trend Modesupporting
confidence: 64%
See 1 more Smart Citation
“…In Figure 7D, the lines following the LVs and PCTS recombination and the adjusted steric component are fitted to the curves, peaking around 2010, with a proportion ranging from 20% to 25%, with an average value of 11.17%, in line with the findings of Qu et al (2019). Previous studies also found that increasing ocean mass accounts for a greater proportion of the drivers of sea level change in the BYECS, and it dominates the contribution to the change in sea level trend (Chang et al, 2017;Qu et al, 2023).…”
Section: Trend Modesupporting
confidence: 64%
“…These findings align with previous conclusions, emphasizing steric sea level as the primary influencing factor of ECS sea level variation. The central and eastern parts of the ECS are influenced by the high-temperature and highsalinity outer seawater introduced by the Kuroshio (Zhang et al, 2014;Chang et al, 2017;Qi et al, 2018;Qu et al, 2023). The Taiwan Strait, due to its shallow depth, is affected by both circulation and local wind (Qi et al, 2017;Liu Z. et al, 2021).…”
Section: Annual Modementioning
confidence: 99%